Gerenciamento de resultados e os fatores determinantes dos custos assimétricos no Brasil - Santos, Sergio Gouveia (2022)
This research aimed to investigate the association between the determinants of asymmetric costs and earnings management by discretionary accruals and real activities in publicly traded Brazilian companies, from 2010 to 2021, using a sample of 134 non-financial companies, distributed among 9 economic sectors of [B]3 – Brasil, Bolsa, Balcão, with accounting data collected at Economática© and on the website of the Brazilian Securities Commission (CVM). Initially, using the model by Anderson, Banker and Janakiraman (2003), an asymmetrical behavior of costs was found for the sample and period delimited, identifying that costs vary by 0.78% for positive variations of 1% in net revenue of sales and only 0.66% for reductions of 1% of revenue. Then, a common vector was estimated that gathers factors that determine the asymmetry of costs pointed out by the cost behavior literature. Thus, using fixed effects panel data, it was verified that the presence of determining factors positively affect discretionary accruals when there is a scenario of revenue reduction for the Modified Jones model of Dechow, Sloan and Sweeney (1995). On the other hand, the results indicate that there is an increase in the use of discretionary accruals due to the decrease in the negative impact of the determinants of cost asymmetry when using Pae's model (2005). However, it was found that the covid-19 pandemic had a positive effect on discretionary accruals, while it negatively affected the use of management by real activities. Therefore, the study contributes with theoretical and empirical evidence that the presence of factors that determine asymmetry in the entity's cost structure can encourage earnings management in periods of decline in the level of activity, as an alternative to alleviate the negative impact of asymmetric costs in performance. Still, it is shown as an indicator for observation and analysis of academics, investors and other market users who use accounting information in their decisions.